Comparison of vascular and respiratory effects of endothelin-1 in the pig - M. G. Clement; M. Dimori; M. Albertini (Mediators of Inflammation)
The haemodynamic and respiratory responses caused by i.v. administration of endothelin-1 (ET-1) (20–100 pmol/kg) were studied in anaesthetized spontaneously breathing pigs. Intravenous bolus administration of synthetic ET-1 (40–100 pmol/kg) caused a transient decrease followed by a long-lasting increase in mean pulmonary arterial pressure and dose dependent vasoconstriction both in the systemic and pulmonary circulations. The effect on pulmonary arterial pressure was biphasic, with an initial transient fall followed by a long-lasting dose dependent increase. A biphasic response of the systemic mean arterial pressure was demonstrated only at a high dose of ET-1 (100 pmol/kg). ET-1 administration did not significantly change breathing pattern or phasic vagal input, but caused a significant decrease in passive compliance. Passive resistances or active compliance and resistances of the respiratory system were not modified. These results suggest that in the pig ET-1 is a more potent constrictor of vascular than of bronchial smooth muscle. The vasoconstrictor activity was greater in the pulmonary than the systemic circulations.